Hubungan Pengasuh Anak dengan Perkembangan Personal Sosial Anak Usia 4 – 6 Tahun di Tk Aisyiah Kota Kupang - Yurissetiowati (HEALTH CARE : JURNAL KESEHATAN, 2021)
Early childhood is a child who is in the age range 0-6 years. Early childhood has a very rapid development. Based on research results, 40% of human development occurs at an early age so that early age is seen as very important and is termed the golden age. Child development is strongly influenced by family factors. There are many factors that can affect the development of children aged 4-6 years, one of which is the caregiver. The purpose of this study was to determine the relationship between caregivers and personal social development of children aged 4-6 years in Aisyiah Kindergarten, Kupang City. This study uses an analytical study with a cross sectional approach. The study population was all children aged 4-6 years in Aisyiah Kindergarten, Kupang City in 2019. The sample of this study was 74 respondents. Data was collected using questionnaires and DDST observation sheets. This study uses the Chi-Square test. The results showed that the caregivers had p-value > 0.05 (p-value = 0.604), which means that there is no significant relationship between the factors of caregivers and the personal social development of children aged 4-6 years. Conclusion There is no positive and significant relationship between caregivers and personal social development of children aged 4-6 years at Aisyiah Kindergarten, Kupang City.